Perhitungan Sumberdaya Batugamping Di Dusun Gudang Garam Arso 4 Distrik Skanto Kabupaten Keerom - Djuardrensi Patabang; Bevie M Nahumury (Jurnal Sains dan Teknologi, 2023)
Keerom Regency is one of the areas that has the potential for Batugamping mineral resources which is quite potential, this is evidenced by the existence of several mining business actors who are carrying out mining activities in the area. Based on the geological map of the Jayapura sheet (Taritatu Sheet) the distribution of limestone potential is quite evenly distributed in the Keerom Regency area. The distribution of limestone potential in Keerom Regency is spread in the Arso 1, Arso 4, Arso 10, Arso 13 areas to Senggi. Based on the results of the initial survey, mining activities in Keerom Regency have not been managed properly, because some mining sites have carried out mining activities but do not yet have legality, namely a mining permit (SIP), do not have a good and correct mine processing plan based on the mining stages, there are still locations where limestone is not yet known distribution, volume and even the amount of resources and reserves. The potential for limestone is a good investment opportunity if it is developed into a community mine that can provide added value to the community. Therefore, it is necessary to have geological mapping activities and also the calculation of resource values. In this case, it concerns the quantity and quality of deposits to be able to provide information as a mineral database for the community as land owners and is also very useful for the Keerom Regency government. This research aims to determine the amount of limestone volume which can later be used as data base information during mining activities. The research also utilized the Surfer 11 application for the creation of topographic maps and to calculate the number of limestone volumes. The research method that will be carried out is the Cross Section Method which is a special Method for types of rock minerals